Instalación de una planta solar de 100 MW para la producción y almacenamiento de energía eléctrica en el sur del Perú - Milla Camacho, César Martín (2024)
The project focuses on implementing a solar power generation plant with a capacity of 200,016 panels of 665 Wp with storage systems, covering an area of 47 hectares. This venture, supported by a Project Finance approach, aims to leverage diversified sources of financing, combining equity and debt. With a budget of USD 94,334,715, the investment includes tangible and intangible assets, along with a working capital fund. The financial structure is distributed with 30% self-funding and 70% debt. The financial analysis projects significant revenue generation, supported by an optimistic selling price and operational efficiency. Additionally, careful risk management addresses political, economic, social, technological, and environmental aspects. The 20-year financial projections reveal robust indicators, including a NPV of $ USD 16,250,092, an IRR of 13.60%, and a payback period of 11 years and 9 months. The project stands out for its sustainable approach, considering environmental aspects such as CO2 emission reduction and waste management. In the pursuit of efficiency, continuous financial resource optimization, exploration of diversification, and staying at the forefront of technological innovations are recommended. Strengthening strategic alliances and ongoing environmental monitoring complement the recommendations to ensure the long-term success of this ambitious solar power generation project.